Neuroprotective Mechanisms of GLP‑1 Pathway Activation in Parkinson’s Disease - Foundations For Future Disease‑Modifying Strategies - Chmiel, Gabriela; Bachurski, Patryk; Kalinowski, Paweł; Międlar, Maja; Muda, Martyna; Pacek, Szymon; Pierzga, Elisabetta; Wiśniewski, Karol Paweł; Witkowski, Paweł; Zarański, Bartosz (Quality in Sport, 2026)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the selective loss of dopaminergic neurons, accumulation of α‑synuclein, mitochondrial dysfunction, neuroinflammation, and systemic metabolic disturbances. While current therapies effectively address motor symptoms, interventions capable of modifying disease progression remain lacking. In recent years, activation of the glucagon-like peptide-1 (GLP‑1) signaling pathway has emerged as a promising neuroprotective strategy in PD. This review focuses on literature published from 2021 onwards, synthesizing mechanistic insights into GLP‑1 receptor agonists (GLP‑1RAs), dual GLP‑1/GIP agonists, and GLP‑1-based microbiome interventions, with an emphasis on their potential to act as disease-modifying therapies by targeting the core pathophysiological processes underlying PD. Given the recent failure of several α-synuclein-targeted monotherapies, GLP-1 pathway activation offers a systems-level alternative capable of addressing multiple convergent drivers of neurodegeneration.